(untitled) (PITIMAS: Journal of Community Engagement in Health, 2025)
Nutritional problems in school children are still quite complex, including overweight and obesity. The cause of nutritional problems in school-age children is unhealthy eating habits which are also influenced by a lack of knowledge about nutrition. Community service activities are carried out to increase student knowledge and emphasize active student participation during the implementation of activities. Community service was carried out at SDN 2 Wates Timur with a total of 28 fifth-grade students as respondents. The activities consisted of a preparation stage, namely screening and initial data collection, the implementation stage included a pre-test, delivery of materials and games using SEGA cards as media and evaluation, namely by giving a post-test. The results obtained showed that the respondents were mostly female, aged 10-11 years and 11% of students were overweight and had unhealthy snacking habits. Education was carried out using PowerPoint media followed by SEGA card games, which were obtained to attract active student participation and were able to answer questions with the SEGA cards provided. Knowledge evaluation through pre- and post-tests obtained an increase in knowledge of 31.7 points. The community service activities went well, were able to attract student activity and were able to increase knowledge about balanced nutrition and healthy snacks.generations.